CO2 efflux from cleared mangrove peat. - Catherine E Lovelock (Public Library of Science (PLoS), 2011)
Background CO(2) emissions from cleared mangrove areas may be substantial, increasing the costs of continued losses of these ecosystems, particularly in mangroves that have highly organic soils. Methodology/principal findings We measured CO(2) efflux from mangrove soils that had been cleared for up to 20 years on the islands of Twin Cays, Belize. We also disturbed these cleared peat soils to assess what disturbance of soils after clearing may have on CO(2) efflux. CO(2) efflux from soils declines from time of clearing from ∼10,600 tonnes km(-2) year(-1) in the first year to 3000 tonnes km(2) year(-1) after 20 years since clearing. Disturbing peat leads to short term increases in CO(2) efflux (27 umol m(-2) s(-1)), but this had returned to baseline levels within 2 days. Conclusions/significance Deforesting mangroves that grow on peat soils results in CO(2) emissions that are comparable to rates estimated for peat collapse in other tropical ecosystems. Preventing deforestation presents an opportunity for countries to benefit from carbon payments for preservation of threatened carbon stocks.